Analog and digital signal processing method using multi‐time‐over‐threshold and FPGA for PET. Issue 9 (17th August 2018) - Kim, Kyu Bom; Choi, Yong; Jung, Jiwoong; Lee, Sangwon; Choe, Hyeok‐jun; Leem, Hyun Tae
Abstract : Purpose: The goal of this study was to develop an analog and digital signal processing method using multi‐time‐over‐threshold (MTOT) and field programmable gate arrays (FPGAs) to extract PET event information by using the internal clock of FPGA ( 350 MHz), without ADC and TDC. Methods: The PET detector modules were composed of a 4 × 4 matrix of 3 × 3 × 20 mm 3 LYSO and 4 × 4 SiPM array. Output charge signals of PET detector modules were amplified and fed into four comparators to generate trigger signals. The energy of the detected gamma ray was calculated by integrating the digitized pulse and the arrival time was determined from the time stamp of the lowest trigger signal by FPGA. The data packet containing energy, time, and position information was stored in list mode on the host computer. Results: The performance of analog and digital signal processing circuits using MTOT method and FPGA was evaluated by measuring energy and time resolution of the proposed method and the values were 19% and 900 ps, respectively. Conclusion: This study demonstrated that the proposed MTOT method consisting of only FPGA without ADC and TDC could provide a simple and cost‐effective analog and digital signal processing system for PET.